SEJARAH DAN PERKEMBANGAN PONDOK PESANTREN - qomariyah, eva; Melin Andini Deski (Al Naqdu, 2024)
Islamic boarding schools are distinctive Islamic educational institutions in Indonesia, with historical roots derived from Hindu-Buddhist traditions and the process of Islamization. This article aims to provide a comprehensive understanding of the history and development of pesantren, from the early days of their establishment to the modern era. Pesantren play an important role in the formation of individual character, the spread of Islam, and the struggle against colonialism. In their development, pesantren have gone through various challenges, including the colonial period, educational discrimination policies, and technological disruption. The modernization of pesantren allows the integration of religious education with the general curriculum and digital technology. This makes pesantren relevant in facing the challenges of globalization, while still maintaining religious traditions. The article also discusses innovations in modern pesantren, such as the application of technology in learning and management, so that pesantren are not only centers of religious education, but also centers of community empowerment. With a historical approach and developmental analysis, this paper offers insight into the future of pesantren as dynamic and adaptive Islamic educational institutions.